Oscillation in tissue oxygen index during recovery from exercise - Yano, T; Afroundeh, R; Shirakawa, K; Lian, C-S; Shibata, K; Xiao, Z; Yunoki, T (Physiological research, 2016)
It was hypothesized that an oscillation of tissue oxygen index (TOI) determined by near-infrared spectroscopy during recovery from exercise occurs due to feedback control of adenosine triphosphate and that frequency of the oscillation is affected by blood pH. In order to examine these hypotheses, we aimed 1) to determine whether there is an oscillation of TOI during recovery from exercise and 2) to determine the effect of blood pH on frequency of the oscillation of TOI. Three exercises were performed with exercise intensities of 30 % and 70 % peak oxygen uptake (V(.)o(2)peak) for 12 min and with exercise intensity of 70 % V(.)o(2)peak for 30 s. TOI during recovery from the exercise was analyzed by fast Fourier transform in order to obtain power spectra density (PSD). There was a significant difference in the frequency at which maximal PSD of TOI appeared (Fmax) between the exercises with 70 % V(.)o(2)peak for 12 min (0.0039+/-0 Hz) and for 30 s (0.0061+/-0.0028 Hz). However, there was no significant difference in Fmax between the exercises with 30 % (0.0043+/-0.0013 Hz) and with 70 % V(.)o(2)peak for 12 min despite differences in blood pH and blood lactate from the warmed fingertips. It is concluded that there was an oscillation in TOI during recovery from the three exercises. It was not clearly shown that there was an effect of blood pH on Fmax.
Keywords: kosterní svaly; zátěžový test; mladý dospělý; svalová kontrakce; biologické hodiny; Adolescent; Oxygen Consumption; lidé; cvičení; Muscle, Skeletal; analýza krevních plynů; Biological Clocks; Male; Exercise Test; Young Adult; Blood Gas Analysis; mužské pohlaví; Muscle Contraction; Exercise; mladiství; spotřeba kyslíku; Humans